Tourism as a decision factor in planing among Brazilian regional airlines - Valente, Flávio José; Lohmann, Guilherme (Revista Turismo em Análise, 2005)
ln the last few years the number of tourist destinations served by domestic regional airlines has significantly decreased in Brazil. In spite of the initiatives of several airlines in launching new air routes, many of them do not succeed. ln order to better understand the reasons for these failures, this article analyses, using secondary data, the context of Brazilian regional airlines and presents the concepts of air route planning proposed by the literature. Primary data, using questionnaires sent to regional airlines, was collected with the purpose of analysing the influence of various factors, notably tourism, on the route planning process. As a result of this research, a systemic model for air route planning at the regional scale is proposed.